Air pollution exposure and prevalence of non-alcoholic fatty liver disease and related cirrhosis: A systematic review and meta-analysis - Xingyi He; Shipeng Zhang; Qinglin Bai; Moshen Pan; Yanjie Jiang; Weiwei Liu; Wei Li; Yuanyuan Gong; Xueping Li (Ecotoxicology and Environmental Safety)
Background and objective: A systematic review and meta-analysis were used to investigate the relationship between air pollution exposure and the prevalence of non-alcoholic fatty liver disease (NAFLD) and its related cirrhosis. Through this study, we hope to clarify the potential public health risks of air pollution as an environmental exposure factor. Methods: Through a comprehensive and systematic search of the EMBASE, PubMed, Web of Science, and Cochrane library databases, studies published up to March 30, 2024, that met the eligibility criteria were identified. The meta-analysis aimed to determine the association between air pollution exposure and NAFLD risk. Subgroup analyses were conducted based on regional economic development after adjusting for confounding factors. The combined odds ratio (OR) was calculated, publication bias was assessed using funnel plots, and consideration was given to heterogeneity among study-specific relative risks. Results: This review included 14 observational studies (including 7 cohort studies and 7 cross-sectional studies) involving 43,475,41 participants. The pooled analysis showed that PM2.5, NOx, PM10, PM2.5–10, passive smoking, PM1, and air pollution from solid fuels were positively associated with the incidence and prevalence of NAFLD and its related cirrhosis. The risk ratios for PM2.5, NOx, PM10, PM2.5–10, passive smoking, and air pollution from solid fuels for NAFLD and its related cirrhosis were 1.33 (95 % CI: 1.25, 1.42), 1.19 (95 % CI: 1.14, 1.23), 1.27 (95 % CI: 1.05, 1.55), 1.05 (95 % CI: 1.00, 1.11), 1.53 (95 % CI: 1.12, 2.09), 1.50 (95 % CI: 0.86, 2.63), and 1.18 (95 % CI: 0.85, 1.63), respectively. In contrast, the risk ratio for O3 was 0.75 (95 % CI: 0.69, 0.83), suggesting that O3 may lower the incidence and prevalence of NAFLD and its related cirrhosis. We also conducted subgroup analyses based on the level of national development to examine the impact of PM2.5 on NAFLD and its related cirrhosis. The results showed that the risk of NAFLD and its related cirrhosis associated with PM2.5 in developing countries was 1.41 (95 % CI: 1.29, 1.53), which was higher than 1.20 (95 % CI: 1.12, 1.29) in developed countries. Conclusion: The study findings show that PM2.5, NOx, PM10, PM2.5–10, passive smoking, PM1, and air pollution from solid fuels can increase an individual’s risk of developing NAFLD and its related cirrhosis; while O3 can reduce the risk. In developing countries, the risk level of NAFLD and its related cirrhosis due to PM2.5 is higher than that in developed countries.